CYP2D6 Genetic Variation and Antipsychotic-Induced Weight Gain: A Systematic Review and Meta-Analysis - Wannasuphoprasit, Yanisa; Andersen, Stig Ejdrup; Arranz, Maria J.; Catalan, Rosa; Jurgens, Gesche; Kloosterboer, Sanne Maartje; Rasmussen, Henrik Berg; Bhat, Anjali; Irizar, Haritz; Koller, Dora; Polimanti, Renato; Wang, Baihan; et al. (Frontiers in Psychology, 2022)
Background: Antipsychotic-induced weight gain is a contributing factor in the reduced life expectancy reported amongst people with psychotic disorders. CYP2D6 is a liver enzyme involved in the metabolism of many commonly used antipsychotic medications. We investigated if CYP2D6 genetic variation influenced weight or BMI among people taking antipsychotic treatment. Methods: We conducted a systematic review and a random effects meta-analysis of publications in Pubmed, Embase, PsychInfo and CENTRAAL that had BMI and/or weight measurements of patients on long-term antipsychotics by their CYP2D6-defined metabolic groups (poor, intermediate, normal/extensive and ultra-rapid metabolizers). Results: Twelve studies were included in the systematic review. All cohort studies suggested that the presence of reduced-function or non-functional alleles for CYP2D6 was associated with greater antipsychotic-induced weight gain, whereas most cross-sectional studies did not find any significant associations. Seventeen studies were included in the meta-analysis with clinical data of 2,041 patients, including 93 poor metabolizers (PMs), 633 intermediate metabolizers (IMs), 1,272 normal metabolizers (NMs) and 30 ultra-rapid metabolizers (UMs). Overall, we did not find associations in any of the comparisons made. The estimated pooled standardized differences for the following comparisons were i) PM versus NM; weight = -0.07 (95%CI: -0.49 to 0.35, p=0.74), BMI = 0.40 (95%CI: -0.19 to 0.99, p=0.19). ii) IM versus NM; weight = 0.09 (95% CI: -0.04 to 0.22, p=0.16) and BMI = 0.09 (95% CI: -0.24 to 0.41, p=0.60). iii) UM versus EM; weight = 0.01 (95% CI: -0.37 to 0.40, p=0.94) and BMI = -0.08 (95%CI: -0.57 to 0.42, p=0.77). Conclusion: Our systematic review of cohort studies suggested that CYP2D6 poor metabolizers have higher BMI than normal metabolizers, but the data of cross-sectional studies and the meta-analysis did not show this association. Although our review and meta-analysis constitutes one of the largest studies with comprehensively genotyped samples, the literature is still limited by small numbers of participants with genetic variants resulting in poor or ultra-rapid metabolizer status. We need further studies with larger numbers of extreme metabolizers to establish its clinical utility in antipsychotic treatment. CYP2D6 is a key gene for personalized prescribing in mental health.